PTU-052 Does Use Of Sedation Affect The Speed At Which Endoscopy Is Performed And Number Of Biopsies Obtained In Barrett's Oesophagus?. (9th June 2014) - Subramaniam, S; Defoe, H; Chitembwe, A; Ferrera, J; Besherdas, K
Abstract : Introduction: Guidelines for Barrett's oesophagus (BE) screening recommend 2 yearly endoscopies with 4 quadrant biopsies every 2cm for BE without dysplasia. There is increasing evidence that longer inspection time of BE segment is associated with increased detection of high-grade dysplasia and oesophageal cancer. In our experience, BE surveillance endoscopies have been undertaken both with and without sedation as no formal guidelines recommend use of one method over the other. Endoscopic procedures may be quicker in the unsedated patient and therefore these are likely to have lower Barrett's inspection time (BIT) and also fewer biopsies than in sedated patients. The aim of our study was to assess the prevalence of sedation use in BE surveillance endoscopy and to determine if this affected the time taken for the procedure and the number of biopsies obtained. Methods: A retrospective analysis of all patients who underwent surveillance endoscopy for BE over a 5 year period (2009–2013) in a large district general hospital in North London were identified using the audit tool on Unisoft Endoscopy reporting software. Data collection was done by endoscopy unit nursing staff. From each report, use of sedation, length of BE and number of biopsies taken from BE segment were recorded. The time taken for each BE endoscopy was also obtained from procedure logbooks. The mean length of time (LOT) per procedure was compared between sedated and unsedated endoscopies using a t test. A multiple linear regression fit was performed on the data using regressors sedation values, length of BE and number of biopsies taken. Results: 181 endoscopies for BE surveillance were performed over 5 years. 37 were excluded as insufficient data was available. Of the 144 endoscopies remaining, 73 were unsedated and 71 with sedation. The mean LOT for sedated compared with unsedated endoscopies was 12.47 min and 10.36 min respectively (p = 0.05, confidence interval= –4.23, 0.01). The average number of biopsies in sedated patients was 3.87 and 3.85 in the unsedated (p = 0.47). The regression was a poor fit (R 2 adjusted = –0.00033) and the overall relationship not significant: F (2, 141) = 0.976, p = 0.38. P values for sedation (p = 0.96) and length of BO (p = 0.16) did not achieve significance either. Conclusion: In our study of patients undergoing endoscopy for BE surveillance, the LOT of endoscopic procedure was greater in patients receiving sedation than unsedated patients. The length of BE or the use of sedation did not have a significant effect on the number of biopsies taken. Sedation use did not affect number of biopsies obtained and therefore may not increase dysplasia detection. We conclude that surveillance for BE patients can be performed without sedation. Disclosure of Interest: None Declared.